Time-to-care metrics in patients with interhospital transfer for mechanical thrombectomy in north-east Germany: Primary telestroke centers in rural areas vs. primary stroke centers in a metropolitan area - Christoph Riegler; Christoph Riegler; Janina R. Behrens; Janina R. Behrens; Janina R. Behrens; Janina R. Behrens; Claudia Gorski; Claudia Gorski; Claudia Gorski; Anselm Angermaier; Anselm Angermaier; Stephan Kinze; et al. (Frontiers in Neurology, 2023)
BackgroundMechanical thrombectomy (MT) is highly effective in large vessel occlusion (LVO) stroke. In north-east Germany, many rural hospitals do not have continuous neurological expertise onsite and secondary transport to MT capable comprehensive stroke centers (CSC) is necessary. In metropolitan areas, small hospitals often have neurology departments, but cannot perform MT. Thus, interhospital transport to CSCs is also required. Here, we compare time-to-care metrics and outcomes in patients receiving MT after interhospital transfer from primary stroke centers (PCSs) to CSCs in rural vs. metropolitan areas.MethodsPatients from ten rural telestroke centers (RTCs) and nine CSCs participated in this study under the quality assurance registry for thrombectomies of the Acute Neurological care in North-east Germany with TeleMedicine (ANNOTeM) telestroke network. For the metropolitan area, we included patients admitted to 13 hospitals without thrombectomy capabilities (metropolitan primary stroke centers, MPSCs) and transferred to two CSCs. We compared groups regarding baseline variables, time-to-care metrics, clinical, and technical outcomes.ResultsBetween October 2018 and June 2022, 50 patients were transferred from RTCs within the ANNOTeM network and 42 from MPSCs within the Berlin metropolitan area. RTC patients were older (77 vs. 72 yrs, p = 0.05) and had more severe strokes (NIHSS 17 vs. 10 pts., p < 0.01). In patients with intravenous thrombolysis (IVT; 34.0 and 40.5%, respectively), time from arrival at the primary stroke center to start of IVT was longer in RTCs (65 vs. 37 min, p < 0.01). However, RTC patients significantly quicker underwent groin puncture at CSCs (door-to-groin time: 42 vs. 60 min, p < 0.01). Despite longer transport distances from RTCs to CSCs (55 vs. 22 km, p < 0.001), there was no significant difference of times between arrival at the PSC and groin puncture (210 vs. 208 min, p = 0.96). In adjusted analyses, there was no significant difference in clinical and technical outcomes.ConclusionDespite considerable differences in the setting of stroke treatment in rural and metropolitan areas, overall time-to-care metrics were similar. Targets of process improvement should be door-to-needle times in RTCs, transfer organization, and door-to-groin times in CSCs wherever such process times are above best-practice models.